Enhancing Quality Using the Inspection Program (EQUIP): A Primer for Radiologists. Issue 3 (30th April 2020) - Gerlach, Karen E; Phalak, Kanchan; Parikh, Jay R
Abstract: The new Enhancing Quality Using the Inspection Program (EQUIP) law places more responsibility for quality assurance on the interpreting radiologists and the lead interpreting physician (LIP). Compliance with the law will require addressing three specific questions related to quality assurance and clinical image corrective action, continued compliance, and ensuring LIP oversight. This process enables the radiologist to exemplify added value through physician leadership, team integration, and improved patient care.